2006
DOI: 10.1029/2006jd007280
|View full text |Cite
|
Sign up to set email alerts
|

Changes in frequency and intensity of daily precipitation over the Iberian Peninsula

Abstract: [1] There is a general consensus within the climate community that any change in the frequency or severity of extreme climate events would profoundly impact nature and society. Such changes can be studied in terms of rainfall indices derived from daily data. The great variability of the rainfall over the Iberian Peninsula and the irregularity of its water regime make any study of the rainfall in this geographical region very interesting. In this work, we contribute some information about the characteristics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 43 publications
3
39
0
2
Order By: Relevance
“…In this case, the annual frequency shows no significant trend during the same period 1975-2002 1960 1965 1970 1975 1980 1985 1990 1995 and Trigo (2007) and Gallego et al (2006), although the data and the period selected for these studies are quite different. Therefore, the reduction in the annual frequency of snow days doesn't seem to be related to an overall decrease of days with precipitation.…”
Section: Correlation With Temperature and Precipitationmentioning
confidence: 91%
“…In this case, the annual frequency shows no significant trend during the same period 1975-2002 1960 1965 1970 1975 1980 1985 1990 1995 and Trigo (2007) and Gallego et al (2006), although the data and the period selected for these studies are quite different. Therefore, the reduction in the annual frequency of snow days doesn't seem to be related to an overall decrease of days with precipitation.…”
Section: Correlation With Temperature and Precipitationmentioning
confidence: 91%
“…From the daily rainfall data, we constructed five categories of rainfall magnitude: no rain, light rain, moderate, intense and very intense, following the method adopted in previous works (Osborn et al, 2000;Osborn and Hulme, 2002;Gallego et al, 2006). This classification was done (1) taking into account the whole year and (2) separately for each season.…”
Section: Resultsmentioning
confidence: 99%
“…If the rainfall distribution has changed, it is necessary to determine whether there are specific sub-periods of time with a similar distribution. This type of treatment was not carried out in certain works that studied the evolution and probability of rainfall exceeding dangerous thresholds (Gallego et al, 2006;Rodrigo, 2010;Müller et al, 2009). These authors found a lack of stationarity in rainfall during the 1951-2002 period, especially in terms of extreme values.…”
Section: Introductionmentioning
confidence: 99%
“…In general, all estimates of this probability are made by assuming stationarity in rainfall series. This assumption is not entirely realistic, especially today, when a large number of scientists claim that climate is changing dramatically (Keeling, 1973;Palmer and Räisänen, 2002;Milly et al, 2002;Cox, 2005). If the rainfall distribution has changed, it is necessary to determine whether there are specific sub-periods of time with a similar distribution.…”
Section: Introductionmentioning
confidence: 99%